Genome, Transcriptome, and Germplasm Sequencing Uncovers Functional Variation in the Warm-Season Grain Legume Horsegram Macrotyloma uniflorum (Lam.) Verdc. - Mahesh, H. B.; Prasannakumar, M. K.; Manasa, K. G.; Perumal, Sampath; Khedikar, Yogendra; Kagale, Sateesh; Soolanayakanahally, Raju Y.; Lohithaswa, H. C.; Rao, Annabathula Mohan; Hittalmani, Shailaja (Frontiers in Plant Science, 2021)
Horsegram is a grain legume with excellent nutritional and remedial properties and good climate resilience, able to adapt to harsh environmental conditions. Here, we used a combination of short and long-read sequencing technologies to generate a genome sequence of 279.12 Mb, covering 83.53% of the estimated total size of the horsegram genome, and we annotated 24,521 genes. De novo prediction of DNA repeats showed that approximately 25.04% of the horsegram genome was made up of repetitive sequences, the lowest among the legume genomes sequenced so far. The major transcription factors identified in the horsegram genome were bHLH, ERF, C2H2, WRKY, NAC, MYB, and bZIP, suggesting that horsegram is resistant to drought. Interestingly, the genome is abundant in Bowman–Birk protease inhibitors (BBIs), which can be used as a functional food ingredient. The results of maximum likelihood phylogenetic and estimated synonymous substitution analyses suggested that horsegram is closely related to the common bean and diverged approximately 10.17 million years ago. The double digested restriction associated DNA (ddRAD) sequencing of 40 germplasms allowed us to identify 3,942 high-quality SNPs in the horsegram genome. A genome-wide association study with powdery mildew identified ten significant associations similar to the MLO and RPW8.2 genes. The reference genome and other genomic information presented in this study will be of great value to horsegram breeding programs. In addition, keeping the increasing demand for food with nutraceutical values in view, these genomic data provide opportunities to explore the possibility of horsegram for use as a source of food and nutraceuticals.